Characterisation of phenolic compounds in processed fibres from the juice industry. (1st April 2015) - Delpino-Rius, Antoni; Eras, Jordi; Vilaró, Francisca; Cubero, Miguel Ángel; Balcells, Mercè; Canela-Garayoa, Ramon
Highlights: Phenolic compounds content was characterised in processed fibres from juice industry. Forty phenolic compounds were identified by UPLC-PDA-FLR-MS/MS in fibres. Bound phenolic acids and proanthocyanidins of fibres were measured in solid residues. Phenolic profiles in fibres were consistent with those in lyophilisates from fruits. Abstract: The content of phenolic compounds was determined in nine industrially processed fibres derived from the juice industry. Apple, peach, and pear as non-citrus fruit fibres were examined, as well as orange peel and flesh, tangerine peel and flesh, and lemon flesh as citrus fruit fibres, and carrot as vegetable fibre. The extractable phenolic profile of all fibres was obtained by UPLC-PDA-FLR-MS/MS. Forty phenolic compounds were identified and their concentrations determined. In addition, bound phenolic acids and proanthocyanidins were measured in solid residues in order to determine the phenolic compounds remaining. Also, to allow the comparison of the profiles and contents in the fresh fruit and fibres, we analysed extractable and bound phenolic compounds in lyophilized peel and pulp from fresh fruit. The profile and phenolic content of the fibres was similar to that of the fresh fruit, except for flavan-3-ols, which registered lower values.